Detoxification, Hydrogen Sulphide Metabolism and Wound Healing Are the Main Functions That Differentiate Caecum Protein Expression from Ileum of Week-Old Chicken - Volf, Jiri; Rajova, Jana; Babak, Vladimir; Seidlerova, Zuzana; Rychlik, Ivan (Animals, 2021)
Sections of chicken gut differ in many aspects, e.g., the passage of digesta (continuous vs. discontinuous), the concentration of oxygen, and the density of colonising microbiota. Using an unbiased LC-MS/MS protocol, we compared protein expression in 18 ileal and 57 caecal tissue samples that originated from 7-day old ISA brown chickens. We found that proteins specific to the ileum were either structural (e.g., 3 actin isoforms, villin, or myosin 1A), or those required for nutrient digestion (e.g., sucrose isomaltase, maltase-glucoamylase, peptidase D) and absorption (e.g., fatty acid-binding protein 2 and 6 or bile acid-CoA:amino acid N-acyltransferase). On the other hand, proteins characteristic of the caecum were involved in sensing and limiting the consequences of oxidative stress (e.g., thioredoxin, peroxiredoxin 6), cell adhesion, and motility associated with wound healing (e.g., fibronectin 1, desmoyokin). These mechanisms are coupled with the activation of mechanisms suppressing the inflammatory response (galectin 1). Rather prominent were also expressions of proteins linked to hydrogen sulphide metabolism in caecum represented by cystathionin beta synthase, selenium-binding protein 1, mercaptopyruvate sulphurtransferase, and thiosulphate sulphurtransferase. Higher mRNA expression of nuclear factor, erythroid 2-like 2, the main oxidative stress transcriptional factor in caecum, further supported our observations.
Keywords: wound healing; chicken; stress response; hydrogen sulphide; caecum; ileum